Comparison of Maturation Stages of Natural Killer Cell Differentiation Culture from Cultured and Freshly Isolated Umbilical Cord Blood Hematopoietic Stem Cells - Wijaya, Samuel Febrian; Lestari, Retno; Rahmawati, Inna; Sianipar, Imelda Rosalyn; Nuraditya, Robby; Fasha, Iqbal; Pratama, Gita; Antarianto, Radiana Dhewayani (Makara Journal of Health Research, 2023)
Background: Natural killer (NK) cells originate from the differentiation of hematopoietic stem cells (HSCs) in the common lymphoid progenitor pathway, and HSCs can be obtained from umbilical cord blood (UCB). Comparative studies of NK cell differentiation between cultured and freshly isolated HSCs are important in the development of NK cell therapy for cancer. This study aimed to compare the maturation stages of NK cell differentiation between cultured and newly isolated HSC samples using interleukin-2 in the absence of feeder cells. Methods: Differentiation cultures were divided into two groups according to HSC source. Giemsa staining and flow cytometry were performed to determine the maturation stages and the presence of NKp46 receptors, respectively. Results: Giemsa staining revealed that the cultured HSC samples produce a higher number and more mature (stage 5) NK cells than the freshly isolated HSC samples. Flow cytometry showed that the NKp46 mean fluorescence intensity significantly differed between the two samples, and a high level of NKp46 activation receptor was found in the isolated samples on day 35. Conclusions: The cultured HSC samples could produce more mature NK cell populations than the freshly isolated HSCs, which will be beneficial for the therapy applications of NK cells derived from UCB HSCs.